Epidemiology and Clinical Outcomes of HIV Infection in South-Central China: A Retrospective Study From 2003 to 2018 - Yue, Tingting; Zhang, Pan; Hao, Yuantao; He, Jianmei; Zheng, Jun; De Clercq, Erik; Li, Guangdi; Huang, Yaxiong; Zheng, Fang (Frontiers in Public Health, 2022)
Objective: HIV epidemiology in South-Central China is rarely reported. This study aims to characterize epidemiological and clinical features of HIV-infected patients in Hunan Province, located in South-Central China, for better management of HIV infections. Methods: This retrospective study retrieved multi-center records of laboratory-confirmed HIV-infected patients in Hunan province. Information on HIV-associated mortality and antiretroviral treatment was also collected. Results: Among 34,297 patients diagnosed with HIV infections from 2003 to 2018, 73.9% were males, 41.3% were older adults (≥50 years), and 71.2% were infected by heterosexual transmission. Despite a slow growth of new HIV infections in the overall population, annual percentages of HIV infections increased in older males (85.3% through heterosexual transmission) and young patients <30 years (39.9% through homosexual transmission). At baseline, serum levels of CD4+ T-cell counts were lower in older adults (191.0 cells/μl) than in young patients (294.6 cells/μl, p-value <0.0001). A large proportion (47.2%, N=16165) of HIV-infected patients had delayed diagnosed (CD4+ T-cell counts < 200 cells/μl) from 2003 to 2018. All-cause mortality (57.0% due to AIDS-related illnesses) was reported among 4411 HIV-infected patients, including 2619 older adults. The 10-year survival rate was significantly lower in elderly males than in other patients (59.0% versus 78.4%, p-value < 0.05). Conclusions: Elderly males are prone to HIV infections with a high risk of HIV-associated fatality. Our findings support early prevention and critical care for elderly populations to control HIV infections.